2016
DOI: 10.4238/gmr15049077
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase gene polymorphisms and susceptibility to systemic sclerosis

Abstract: ABSTRACT. The major pathological hallmark of the systemic sclerosis (SSc) is skin and internal organ fibrosis, which results from normal tissue architecture alterations and extracellular matrix (ECM) protein deposition. ECM components are degraded by matrix metalloproteinases (MMP). Promoter region polymorphisms in MMP genes may influence gene expression, resulting in an imbalance between ECM protein production and degradation. Here, we analyzed MMP1 -1607 1G/2G (rs1799750), MMP3 -1171 5A/6A (rs3025058), and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…They also indicated that rs1799750 polymorphism increased the MMP1 expression in vitro [ 19 ]. Rech et al [ 20 ] uncovered that MMP-1 gene variants were associated with systemic sclerosis. A host of studies also demonstrated that MMP-1 gene rs1799750 polymorphism was related to cancer susceptibility, such as leukemia [ 21 ] and gastric cancer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also indicated that rs1799750 polymorphism increased the MMP1 expression in vitro [ 19 ]. Rech et al [ 20 ] uncovered that MMP-1 gene variants were associated with systemic sclerosis. A host of studies also demonstrated that MMP-1 gene rs1799750 polymorphism was related to cancer susceptibility, such as leukemia [ 21 ] and gastric cancer [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies focused on the genetic factors. Associations of HLA DRB104 and single nucleotide polymorphisms of matrix metalloprotease 3 that involve extracellular matrix protein deposition have been reported, as have single nucleotide polymorphisms of the plasma protein α‐2‐HS‐glycoprotein displaying interaction with calcium phosphate, with ectopic vascular calcification inhibition and calcinosis in SSc 9 …”
Section: Discussionmentioning
confidence: 99%
“…The significant component of calcinosis in SSc is calcium hydroxyapatite 3 . Several mechanisms of calcinosis in SSc have been reported: chronic hypoxemia, 4 repetitive injury due to peripheral circulatory insufficiency, impaired limb extension caused by skin sclerosis, local tissue structural damage, 5 genetic factors, 6‐9 increased production of tumor necrosis factor‐α, interleukin‐1, interleukin‐6, and other inflammation‐induced cytokines, 10 and imbalance between hypoxia‐induced angiogenic factors (such as vascular endothelial growth factor and platelet‐derived growth factor) and anti‐angiogenic factors (such as angiostatin and endostatin) 11 . Clinically, risk factors for calcinosis in SSc have been reported to be associated with longer duration of morbidity, 12 anti‐centromere antibody positivity, 2 limited‐type SSc, 2 and skin ulcers 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Along with several other MMPs and their inhibitors, levels of MMP-1 show close association with SSc, and we found that gene expression differed between dSSc and lSSc patient profiles ( Fig 6 ). Serum levels of MMPs are increased in a subset of patients [ 57 ], polymorphisms are associated with various clinical features of disease [ 58 ], and anti-MMP1 antibodies are elevated in lSSc patients [ 59 ]. To our knowledge, this is the first study indicating that transcript levels of MMP1 may differ between lSSc and dSSc patients.…”
Section: Discussionmentioning
confidence: 99%